Can the anaesthetic induced liquid-to-gel phase transition temperature depression be behind the molecular mechanism of general anaesthesia? - Hantal, György; Bánovská, Sára; Varga, Lukács; Fábián, Balázs; Mihály, Judith; Jedlovszky, Pál (Journal of Molecular Liquids, 2024)
We report differential scanning calorimetry (DSC) measurements and extensive computer simulations to determine the gel (Lβ’) to liquid crystalline (Lα) phase transition temperature of the neat 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) membrane as well as DPPC membranes containing different amount of general anaesthetics of various kinds. In addition, measurements are reported on liposomes consisting of molecules that are chemically or, at least structurally similar to certain general anaesthetics, but lack the anaesthetic effect themselves. The aim of the study is to test one of the competing hypotheses that aims at explaining the molecular mechanism of general anaesthesia by relating it to the anaesthetic-induces depression of the temperature of the aforementioned phase transition. Our results, however, do not confirm this conjecture. Thus, while diethyl ether, a well-known general anaesthetic is found not to induce any depression of the phase transition temperature, carbon tetrachloride, a molecule having no anaesthetic effect induces a larger decrease of this temperature than any general anaesthetic considered here. Furthermore, the computer simulations performed reveal that, in fact, none of the two conditions lying behind this conjecture, i.e., that anaesthetics are ideally dissolved in the Lα but do not dissolve at all in the Lβ’ phase, are satisfied. Therefore, we rule out not only a causal relation, but even a simple correlation between the membrane phase transition depression caused by dissolved molecules and the phenomenon of general anaesthesia.
CRIS-Team Scopus Importer:2024-10-25
Keywords: DPPC bilayer; DSC measurements; General anaesthesia; Molecular dynamics simulation; Phase transition point depression

Computer Simulation Insights into the Chemical Origins of Life: Can HCN Enrichment on Interstellar Amorphous Ice Be a Starting Point? - Tóth Ugyonka, Helga; Hantal, György; Szőri, Milán; Jedlovszky, Pál (ACS Earth and Space Chemistry, 2024)
The adsorption of HCN at the surface of low-density amorphous (LDA) ice and its dissolution in the bulk LDA phase is studied by grand canonical Monte Carlo (GCMC) simulations at the temperatures of 50, 100, and 200 K, characteristic of different domains of the interstellar medium (ISM). Dissolved and adsorbed molecules are distinguished using the identification of the truly interfacial molecules (ITIM) method. The results reveal that the adsorption is monomolecular and the adsorption monolayer is only partially saturated at the point of condensation of HCN. The surface coverage corresponding to the saturated adsorption monolayer is estimated to be 9.8 ± 0.3 μmol/m2, providing a better estimate for this quantity than the crude approximation used in evaluating certain experiments. For the entropy of the condensed (glassy) phase of HCN, the simulations provide the value of 17.37 J/(mol K). The adsorption isotherms deviate considerably from the Langmuir shape, revealing that non-negligible interaction occurs between the adsorbed HCN molecules. The adsorption is found to be primarily governed by the dipolar interactions both between the surface water and adsorbed HCN molecules and between HCN neighbors within the adsorption layer. The heat of adsorption at infinitely low surface coverage is estimated to be −49.4 ± 3.9 kJ/mol. Further, the isosteric heat of adsorption at finite coverages is calculated in the entire range of surface coverages. In clear contrast with the adsorption, the dissolution of the HCN molecules remains ideal up to the point of condensation. This indicates that, in spite of the surprisingly large HCN concentrations reached, the HCN-HCN interaction is negligible in the bulk LDA phase. Further, contrary to its adsorption, the dissolution of HCN in LDA ice turns out to be an endothermic process. Finally, our results concerning the adsorption of HCN are not incompatible with the possibility of the oligomerization reaction of the HCN molecules, leading to the prebiotic formation of certain building blocks of biological macromolecules, under interstellar conditions at the LDA surface. Further, assuming that upon approaching the Earth, the transformation of the LDA phase with increasing temperature to liquid water goes through the thermodynamically stable crystalline (Ih) ice phase, which does not dissolve HCN molecules, the presumed expulsion of HCN to the ice surface could provide an additional window of opportunity for their oligomerization.
CRIS-Team Scopus Importer:2024-03-29
Keywords: adsorption; chemical evolution; computer simulation; grand canonical Monte Carlo; HCN; interstellar chemistry; LDA ice

Docking Structures Induced by Substitution Motifs of Softwood Xylan at Various Cellulose Surfaces - Hantal, György; Salmén, Lennart; Hinterstoisser, Barbara (Biomacromolecules, 2025)
To understand xylan-cellulose interactions in softwood, the adsorption behavior of hexameric softwood xylan proxies with various substitutions was analyzed on the three surfaces of a hexagonal cellulose microfibril. The study found that all surfaces could bind xylan motifs, showing equally high affinity for the hydrophilic (110) and hydrophobic (100) surfaces and significantly lower affinity for the hydrophilic (11̅0) surface. Unsubstituted xylose hexamers had the highest affinity and most ordered adsorption structures, while substitutions generally reduced the affinity and regularity. An exception was a motif with two glucuronic acids two residues apart, which displayed high affinity and increased tendency to adopt a 2-fold screw on hydrophilic surfaces. Surface affinity correlated with the tightness of xylan-cellulose associations and the ratio of the xylan-cellulose to xylan-water interaction energies. Novel methods to quantify backbone conformations were proposed. Future work should address differences in simulation models and explore the competition between xylan and glucomannan for cellulose surfaces.
CRIS-Team Scopus Importer:2025-02-14

Influence of molecular hydrogen on bulk and interfacial properties of three imidazolium-based ionic liquids by experiments and molecular dynamics simulations - Zhai, Ziwen; Hantal, György; Cherian, Arsha; Bergen, Alexander; Chu, Junyu; Wick, Christian; Meyer, Karsten; Smith, Ana-Suncana; Koller, Thomas Manfred (International Journal of Hydrogen Energy, 2024)
Despite the presence of molecular hydrogen (H2) in various technical applications involving ionic liquids (ILs), its effect on the bulk and interfacial properties of ILs is poorly understood. The present study investigates the influence of dissolved H2 on the viscosity, surface tension, and phase composition of three imidazolium-based ILs by experiments and Molecular Dynamics (MD) simulations between (303 and 393) K from (0.1 to 31) MPa. The surface light scattering and pendant-drop experiments showed for all three ILs that the saturated liquid viscosity does not significantly change with increasing H2 pressure, while the surface tension decreases about 5% at 8 MPa. The MD simulations could be used to clarify microscopic origins for the behavior of the macroscopic properties. They revealed not only a compensation of compression and solvation effects due to hydrostatic pressure and dissolved H2 on the viscosity, but also a weak enrichment of H2 at the IL-gas interfaces.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Experiments; Hydrogen; Ionic liquids; Molecular dynamics simulations; Surface tension; Viscosity

Spatial organization of the ions at the free surface of imidazolium-based ionic liquids - Tóth Ugyonka, Helga; Hantal, György; Szilágyi, István; Idrissi, Abdenacer; Jorge, Miguel; Jedlovszky, Pál (Journal of Colloid and Interface Science, 2024)
Hypothesis: Experimental information on the molecular scale structure of ionic liquid interfaces is controversial, giving rise to two competing scenarios, namely the double layer-like and “chessboard”-like structures. This issue can be resolved by computer simulation methods, at least for the underlying molecular model. Systematically changing the anion type can elucidate the relative roles of electrostatic interactions, hydrophobic (or, strictly speaking, apolar) effects and steric restrictions on the interfacial properties. Simulations: Molecular dynamics simulation is combined with intrinsic analysis methods both at the molecular and atomic levels, supplemented by Voronoi analysis of self-association. Findings: We see no evidence for the existence of a double-layer-type arrangement of the ions, or for their self-association at the surface of the liquid. Instead, our results show that cation chains associate into apolar domains that protrude into the vapour phase, while charged groups form domains that are embedded in this apolar environment at the surface. However, the apolar chains largely obscure the cation groups, to which they are bound, while the smaller and more mobile anions can more easily access the free surface, leading to a somewhat counterintuitive net excess of negative charge at the interface. Importantly, this excess charge could only be identified by applying intrinsic analysis.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Computer simulation; Imidazolium-based liquids; Interfacial structure; Intrinsic surface; Ionic liquids; Liquid surface; Self-association

The Surface of Imidazolium-Based Ionic Liquids Consists of Two Interfaces - Tóth Ugyonka, Helga; Hantal, György; Szilágyi, István; Idrissi, Abdenacer; Jorge, Miguel; Jedlovszky, Pál (Journal of Physical Chemistry Letters, 2025)
Room temperature ionic liquids (RTILs) are important in a myriad of applications and exhibit fascinating properties arising from a delicate interplay between their ionic and apolar groups. Here, using molecular simulations coupled with intrinsic surface analysis, we reveal how this interplay is responsible for the unique properties of the RTIL surface. Our results show that this surface can be viewed as a superposition of two “interfaces”, one between a hydrophobic layer of cation alkyl chains and the vapor phase, and another between that hydrophobic layer and an ionic fluid composed of polar groups of the cations and anions. Remarkably, the properties of this ionic surface are practically independent of the cation alkyl chain length, suggesting they are a universal feature of imidazolium-based RTILs. This finding has potential implications in the selection and design of RTIL systems for separation applications, which depend on interactions between penetrant molecules and the RTIL surface.
CRIS-Team Scopus Importer:2025-02-28